Electrical Contacts - 2000. Proceedings of the Forty-Sixth IEEE Holm Conference on Electrical Contacts (Cat. No.00CB37081)
DOI: 10.1109/holm.2000.889914
|View full text |Cite
|
Sign up to set email alerts
|

Erosion and contact resistance performance of materials for sliding contacts under arcing

Abstract: In our previous work we have investigated copper sliding switching contacts for automotive power applications. In order to improve their reliability, we have studied in this present paper, alternative materials to copper such as silver based materials (Ag, AgSn02, AgC and AgCNi). Their performance was evaluated by measuring mass variations and contact resistance stability during sliding. The contacts are operated in a test machine during 50,000 sliding operations, under inductive loads which produce long arcs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(1 reference statement)
0
0
0
Order By: Relevance
“…Many studies [1, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] have reported that polarity (the effect of the current-flow direction) has a significant influence on the friction, the contact resistance or the wear of contact surfaces. However, not many studies have looked at this effect in depth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies [1, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] have reported that polarity (the effect of the current-flow direction) has a significant influence on the friction, the contact resistance or the wear of contact surfaces. However, not many studies have looked at this effect in depth.…”
Section: Introductionmentioning
confidence: 99%
“…However, the opposite effect of polarity can be detected depending on the contact material combination. Studies researching metal/metal [10,11,17] and metal-graphite/metal [1, 16,23] contacts usually see higher wear rates for the positively biased brush or contact surface, while for graphite/metal contacts the negative graphite surface usually exhibits higher wear [8,13,14,23]. Nakagura and Sawa studied the copper-graphite and carbon brush on a copper commutator in air and gasoline.…”
Section: Introductionmentioning
confidence: 99%